Mast-Cell-Derived TNF Amplifies CD8(+) Dendritic Cell Functionality and CD8(+) T Cell Priming - Dudeck, Jan; Ghouse, Shanawaz Mohammed; Lehmann, Christian; Hoppe, Anja; Schubert, Nadja; Nedospasov, Sergei A.; Dudziak, Diana; Dudeck, Anne (Cell Reports, 2015)
Mast cells are critical promoters of adaptive immunity in the contact hypersensitivity model, but the mechanism of allergen sensitization is poorly understood. Using Mcpt5-CreTNF(FL/FL) mice, we show here that the absence of TNF exclusively in mast cells impaired the expansion of CD8(+) T cells upon sensitization and the T-cell-driven adaptive immune response to elicitation. T cells primed in the absence of mast cell TNF exhibited a diminished efficiency to transfer sensitization to naive recipients. Specifically, mast cell TNF promotes CD8(+) dendritic cell (DC) maturation and migration to draining lymph nodes. The peripherally released mast cell TNF further critically boosts the CD8(+) T-cell-priming efficiency of CD8(+) DCs, thereby linking mast cell effects on T cells to DC modulation. Collectively, our findings identify the distinct potential of mast cell TNF to amplify CD8(+) DC functionality and CD8(+) T-cell-dominated adaptive immunity, which may be of great importance for immunotherapy and vaccination approaches.
EVALuna2:19558